The Word (kalima) in The Holy Quran It’s Meanings, Forms, Categories, Types, Sections, Characteristics, And Laws - Bakrou, Khaled (Journal of Islamic Sciences, 2018)
God said" :And if all the trees on the earth were pens and the sea (were ink wherewith to write)، with seven seas behind it to add to its (supply)، yet the Words of Allah would not be exhausted. Verily, Allah is AllMighty, AllWise". [Luqman: 31/27]. If the trees of the earth are pens, and they will be set up to write the God’s words, The God’s words will not run out, and its wonders will not be fade. "This is why the Quranic word is explained as a wondrous. Based on these words of Imam Al-Razi in the interpretation of the verse, which established the argument that the meanings of the Quranic words and its draw mode was in sky. The research comprehensive reviewed in shapes of this wondrous word. And it is concerned on the word (kalima) in the Holy Quran. It presents its forms, meanings, sections, types, and categories, and provides us with statistics on the frequency of the four forms in the Holy Quran. These forms are ) kalima, kalimat, klma, alkalim (. In addition to a detailed presentation of the Qur’anic word, definition, importance, meaning, drawing, and summarizing the most important characteristic of God’s words. The importance of research is that it extracts laws to God’s words, for every form of the word (kalima), And gives group of meanings, benefits, concords, facts, results, The most important of which is that the word (kalima) in most of the Qur’anic texts in which it was mentioned, was explicitly attributed to the God’s name, or with addition to him. It is an important sign that everything in the universe is the creation of God, that God is the Creator of everything, and everything was created by the God’s Word, and follows God’s Word, and subjects to them.